Home Rule : National Sovereignty and the Separation of Natives and Migrants - Sharma, Nandita Rani, 1964- (Book collections on Project MUSE., 2020)
"In HOME RULE Nandita Sharma examines the twentieth-century transition from a world system based on empires to one based on nations. The UN Charter of 1945 endorsed the rights of self-governance to peoples on their land. At the end of World War II many people were displaced or had become refugees. Sharma asks why such migrants would not have the same rights as those still on their land. She traces the history of the development of the categories of migrants, local residents, and indigenous peoples back through colonial administration, showing what these categories actually were designed to accomplish. She argues that while the desire for national self-governance might have seemed like an answer to colonial rule, it has done more for liberal capital than it has for actual decolonization. Accounts of settler colonialism and indigenous nationhood have often depended on this same self-rule on the land. Sharma's account will complicate such claims in seeing them as part of a wider moment in world history. HOME RULE begins with a historical investigation into the transition from direct rule to indirect rule in imperial British India. Sharma then explores the transitions in the way that European Empire exercised control through the periods of colonization, independence, and neoliberalism. While moving through this history, Sharma catalogues the various laws and economic policies that regulated the mobility of labor, and the nationalist messages that justified those laws and policies. Sharma then demonstrates in chapters 5-7 how nationalism, though originating in Euro-American nation-states, became a prominent feature in movements against colonization and for self-determination. It is in these chapters that Sharma shows how the adoption of the nation-state model contained the potential of these movements for self-determination. Sharma concludes HOME RULE with the proposal to reject borders and nations as a whole as a means of questioning more deeply the limits of nationalism in achieving liberation for former colonies. This book will be of interest to scholars of postcolonial theory, history, social theory, sociology, anthropology, and geography"--